Comparison of various dermatoglyphic methods of collecting and preserving fingerprints for study purpose - Ramakrishnan, Vidhya (International Journal of Research in Medical Sciences, 2022)
Background: This study is an attempt to compare the various methods of recording fingerprints and to find the most accurate, feasible, non-toxic, inexpensive and permanent method of recording and preserving dermatoglyphic prints for study and research purpose. Methods: 100 adult volunteers from KLE Society’s Institute of Dental Sciences participated in this study. They were asked to clean and dry their hands. Then they were randomly allotted to one of the 5 groups. The right thumb was used as a reference and prints were obtained by the method specified to the group. The prints obtained from different methods were compared for clarity, precision, ease of preservation. Results: Prints obtained by the ink method were clear and accurate. Adhesive tape methods were difficult to obtain but yielded good prints. Machine oil method was relatively easy but did not yield good prints. Photographic prints were clear. Digital finger printing method gave the most accurate and reliable prints. All these prints were compared and they were rated based on clarity, accuracy and ease of recording and preserving. Conclusions: Every method employed has its own advantages and disadvantages. Based on the type of study and the parameters to be assessed, different methods of collecting fingerprints can be employed.